"I have the child who has something else." Entering the Worlds of How Mothers Make Sense of `Diagnosis' within the context of their Child with a Rare or Undiagnosed Neurodevelopmental Condition in Ireland: An Interpretative Phenomenological Analysis - Milofsky, Beth (Trinity College Dublin. School of Linguistic Speech & Comm Sci. Discipline of Clin Speech & Language Studies, 2024)
Information on the experiences of parents whose children have rare or undiagnosed conditions is particularly lacking in Ireland. It can be hypothesised that these parents experience a unique set of challenges, in comparison to parents of children with other conditions which are more widely understood. Their journey may include lack of professional and public knowledge, uncertainty, isolation, delays in genetic testing, lack of a clear diagnosis or disease trajectory, and/or difficulties identifying appropriate management and services. To the researcher's knowledge, this is the first study to exclusively explore how mothers make sense of `diagnosis? where their child has a rare or undiagnosed condition, living in Ireland. The nature of the study also afforded the opportunity to interrogate `diagnosis', as a phenomenon, more broadly. The study ultimately aimed to better understand the experience of these mothers to inform Irish healthcare services and enhance the experience of children and families. This is a qualitative research study using interpretative phenomenological analysis (IPA) as the primary analytic methodology, with borrowed insights from narrative analysis. Five mothers participated in individual in-depth semi-structured interviews with the researcher, via an online conferencing platform. One participant volunteered a subsequent written update, which was included in the data set. I identified six general experiential themes (GETs) from my iterative analysis of the data, with several subthemes, as follows: (1) Entering the world of diagnosis: "There's nothing wrong but everything is wrong"; (2) The world of rare disease: What's in a name?; (3) The world of mothers in healthcare systems: 'You adjust to it because you have to, because your child needs you to'; (4) Etching of the mothers' inner worlds: 'I'll never forget'; (5) Living within a sociocultural world: Constructions and perceptions of `disability' - 'Why do I have to use the word disorder to describe my child?', and finally, (6) The world of the sibling: 'Second fiddle'. This study provides rich insights into the lifeworlds of mothers on the phenomenon being studied. Commonalities in the mothers' experiences show there is a need for greater understanding and knowledge of rare disease amongst healthcare professionals, improved healthcare communications and processes, a designated support group for parents of children with undiagnosed conditions in Ireland and provision of sibling supports. The findings are contextualised within the extant literature, and a case is made for an expansion of our understanding of the meaning of the term `diagnosis' to, not only suggest category and process, but also to include the dimension of diagnosis as essentially `relative?, as will be critically justified. The study is also an exemplar of IPA. The findings have implications for healthcare professions and medical undergraduate and postgraduate education. The findings also have implications for the enhancement of and suggestions for healthcare communication, clinical procedures, and healthcare policy, more generally. Further research is recommended on the meaning of `diagnosis? for rare and undiagnosed conditions from a diverse group of parents, and the perspectives of fathers, siblings, and healthcare professional perspectives in Ireland. The study, taken together with future research, may contribute to global health policy development in the area of rare disease.
APPROVED
Keywords: rare disease; undiagnosed conditions; diagnosis; maternal experience of disability for their child; interpretative phenomenological analysis; narrative analysis; illness narrative